Cellular Target Proteome in Breast Cancer Cells of an Oplopane Sesquiterpenoid Isolated from Tussilago farfara - Song, Kwangho; Nho, Chu Won; Ha, In Jin; Kim, Yeong Shik (AMER CHEMICAL SOC, 2020)
Tussilago farfara is a traditional herbal medicine used to treat coughs, bronchitis, and asthma. Its bioactive compounds include sesquiterpenoids with anti-inflammatory, antiproliferative, neuroprotective, and other effects. Biochemical studies have highlighted the mechanisms of action, but the investigations of related molecular pathways have not specified direct molecular targets. Therefore, this study profiled cellular target proteins of a sesquiterpenoid isolated from T. farfara using quantitative chemical proteomics in MDA-MB-231 and MCF-7 human breast cancer cells. Compound 8, 7 beta-(3'-ethyl-cis-crotonoyloxy)-1 alpha-(2'-methyl butyryloxy)-3,14-dehydro-Z-notonipetranone, exhibited potent antiproliferative activity based on its alpha,beta-unsaturated carbonyl moiety, and its potential cellular target proteins were identified using a compound 8-based clickable probe. Among >200 identified proteins, 17 showed enrichment ratios of >3 in both cell lines, while recombinant 14-3-3 protein zeta and peroxiredoxin-1 were verified using isothermic calorimetry and their alkylation sites. Considering the interaction between the alpha,beta-unsaturated carbonyl moiety of compound 8 and cysteine residues of the proteins, peptides containing Cys25 and Cys94 of 14-3-3 protein zeta and Cys83 of peroxiredoxin-1 were significantly reduced by this sesquiterpene ester. Although the results did not elucidate the effects of compound 8 in breast cancer cells, identification of potential target proteins contributes to enhanced understanding of its antiproliferative and anti-inflammatory effects.
Keywords: PEROXIREDOXIN 1; FLOWER BUDS; LABEL-FREE; IN-VIVO; ENZYMES; DERIVATIVES; CYSTEINE; TOOLS; KEAP1; ACID